Printed H-shaped antenna for wireless network - Mansor, Nur Syahirah; Abdul Rahim, Nawal (2013)
H-shaped patch antenna suitable for wireless and satellite communication is presented. The new antenna has some advantages compared to conventional microstrip patch antennas, such as small size, a fewer number of modes, no harmonics resonance, and the provision of pure reactive impedances at its harmonics that can result in increasing the transmitter efficiency. The basic principles and design procedure are introduced. Two antennas at two different frequencies, 4 and 10 GHz, are designed, fabricated and measured. The measured results show a good agreement with the predicted ones. Simulation is done using two different simulation technique, the circuit model derived from the Transmission Line Model and is compared with another simulation set using Method of Moment. After optimized process, a good design of patch antenna fabricated using FR4 of 1.6mm thickness and feed using proximity coupling method. The fabricated patch is tested using Vector Network Analyzer (VNA) to evaluate its performed measurement result in SI 1, VSWR and bandwidth. To match the input resistant, the output of the feeder line was accurate at 50Q so that it can test at the lab using Vector Network Analyzer (VNA) to measure the network parameters of electrical networks.